The graveyard book - Gaiman, Neil.; McKean, Dave (New York : HarperCollins, 2008)
Nobody Owens is a normal boy, except that he has been raised by ghosts and other denizens of the graveyard.
Keywords: Dead -- Juvenile fiction; Supernatural -- Juvenile fiction; Cemeteries -- Juvenile fiction; Science fiction